Chitin-Induced Gene Expression in Secondary Metabolic Pathways of Streptomyces coelicolor A3(2) Grown in Soil - Nazari, Behnam (American Society for Microbiology, 2013)
Microarray analyses revealed that the expression of genes for secondary metabolism together with that of primary metabolic genes was induced by chitin in autoclaved soil cultures of Streptomyces coelicolor A3(2). The data also indicated that DasR was involved in the regulation of gene expression for chitin catabolism, secondary metabolism, and stress responses.